2019
DOI: 10.5194/acp-2019-757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Particulate organic nitrates in eastern China: variation characteristics and effects of anthropogenic activities

Abstract: <p><strong>Abstract.</strong> Particulate organic nitrates (PONs) constitute a substantial fraction of secondary organic aerosols and have important effects on the reactive nitrogen budget and air quality. Laboratory studies have revealed the non-negligible influence of the interactions between anthropogenic pollutants and biogenic volatile organic compounds (BVOCs) on the formation of PONs. In this study, the contents of specific PONs, including monoterpene hydroxyl n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have confirmed that the abundance of PONs is significantly influenced by the physical and chemical characteristics of aerosols, mixing ratios of precursors and oxidants, meteorological parameters, and anthropogenic activities [13,15,16]. BVOCs, such as oleic acid, isoprene, sesquiterpene, and monoterpenes, are recognized as key precursors of PONs, and the formation of PONs varied largely depending upon BVOC species [16]. Elevated concentrations of both BVOCs and NO x contribute to an increase in PON production through the oxidation of BVOCs in the presence of NO x during photochemical processes, as noted in the studies by Lee and Li [3,17].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous studies have confirmed that the abundance of PONs is significantly influenced by the physical and chemical characteristics of aerosols, mixing ratios of precursors and oxidants, meteorological parameters, and anthropogenic activities [13,15,16]. BVOCs, such as oleic acid, isoprene, sesquiterpene, and monoterpenes, are recognized as key precursors of PONs, and the formation of PONs varied largely depending upon BVOC species [16]. Elevated concentrations of both BVOCs and NO x contribute to an increase in PON production through the oxidation of BVOCs in the presence of NO x during photochemical processes, as noted in the studies by Lee and Li [3,17].…”
Section: Introductionmentioning
confidence: 86%
“…PONs form primarily as a result of the secondary oxidation of anthropogenic or biogenic volatile organic compounds (BVOCs) when exposed to radicals of other oxidizing agents in the presence of NO x [13,14]. Previous studies have confirmed that the abundance of PONs is significantly influenced by the physical and chemical characteristics of aerosols, mixing ratios of precursors and oxidants, meteorological parameters, and anthropogenic activities [13,15,16]. BVOCs, such as oleic acid, isoprene, sesquiterpene, and monoterpenes, are recognized as key precursors of PONs, and the formation of PONs varied largely depending upon BVOC species [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the heterogeneous incidence pattern of pneumoconiosis depends mainly on the prevalence of risk factors in different regions. For example, the National Occupational Disease Report of 2016 indicated that 26,873 new cases of pneumoconiosis were recorded in China, of which 54.3% were coal workers' pneumoconiosis and 39.7% were silicosis [12]. Whereas Australia is one of the countries with the highest incidence rates of asbestos-related lung disease across the world [13,14].…”
Section: Introductionmentioning
confidence: 99%